AB1468-HPR Long term (1-yr) efficacy and safety of single 6ml injection of hylan G-F 20 in indian patients with symptomatic knee OA. (23rd January 2014) - Pal, S.; Thuppal, S.; Reddy, K.J.; Avasthi, S.; Aggarwal, A.; Bansal, H.; Mohanasundaram, S.; Bailleul, F.
Abstract : Background: Single 6mL intraarticular injection of hylan GF 20 is safe and effective with significant reduction in walking pain up to 52 weeks compared to baseline in this prospective, open label, multicentre study. Objectives: The study aims to evaluate the efficacy and safety of 6mL intraarticular (IA) injection of hylan GF 20 over a period of 52 weeks in patients with symptomatic knee osteoarthritis (OA) in standard clinical practice. Methods: This prospective, open label, multicentre (36 Indian centres) study is conducted in patients with symptomatic, predominant tibio-femoral OA (Kellgren-Lawrence grade [KLG] I–III), aged ≥30 years with moderate to severe walking pain (WOMAC A1, baseline VAS score between 40-80mm). Patients received a single 6 mL injection of hylan GF 20 at baseline and were evaluated at Weeks 1, 4, 12, 26, 39 and 52 for efficacy variables (WOMAC, SF-12, patient and clinician observer global assessments [PTGA and COGA, respectively] and impact on concomitant OA medication) and safety variables (examination of injected knee and adverse events [AEs]). The primary endpoint was change in WOMAC A1 subscore at week 26 from baseline. At week 26, 39 or 52 weeks, based on physician's assessment of safety and efficacy during the primary phase of the study, patients were offered participation in an additional 4-week Repeat Treatment Phase to evaluate safety and short term efficacy. Results: Out of 394 patients [mean age: 57.6±9.8 years; mean BMI: 27.66±4.48; female/male: 72/28%; KLG I: 5.1%; II: 38.3%; III: 56.6%] enrolled, 369 patients were evaluated at Week 52. The WOMAC A1 sub score (walking pain) significantly decreased as early as Week 1 after the injection and was down by 45.7% from 60.4±10.31mm at baseline to 32.4±18.88mm at Week 26 and 27.8±18.10 mm (-53.1%) at Week 52 (p<0.0001). WOMAC A pain and WOMAC C function scores decreased from baseline respectively of 50.8% and 45.5% at Week 52 (p<0.0001). The percentage of responders to treatment (as defined by at least 10mm reduction in WOMAC A1 score from baseline and no target knee AE) was 76.6% and 80.7% at Week 26 and 52 respectively. PTGA, COGA and quality of life (SF-12) scores also significantly improved over 52 weeks (p<0.0001). No significant change in concomitant medication usage was observed by Week 52 vs baseline. A total of 26 treatment-emergent target knee AEs were reported in 23 of 394 patients (5.8%) over 52 weeks. The most commonly reported treatment-emergent target knee AE was arthralgia (n=16; 4.1%). One patient had unrelated treatment-emergent target knee SAE of arthritis. Out of 11 patients retreated (2.8%), 6 patients were retreated at Week 26 and remaining 5 patients were retreated at Week 52. In these few patients who were retreated the second injection was found to be safe and effective 4 weeks after re-injection. Conclusions: This study demonstrates that in Indian clinical practice a single 6mL IA injection of hylan GF 20 has a favourable safety profile and is effective in the treatment of symptomatic knee OA up to 1 year post-injection in most patients with significant long term improvement in patient outcomes. Disclosure of Interest: S. PAL Grant/Research support from: Genzyme, S. THUPPAL Grant/Research support from: Genzyme, K. REDDY Grant/Research support from: Genzyme, S. AVASTHI Grant/Research support from: Genzyme, A. AGGARWAL Grant/Research support from: Genzyme, H. BANSAL Employee of: Genzyme, S. MOHANASUNDARAM Employee of: Genzyme, F. BAILLEUL Employee of: Genzyme